2021
DOI: 10.1002/ange.202016899
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Induced Intramolecular Double Dearomative Cycloaddition of Arenes

Abstract: Herein we report visible‐light‐induced intramolecular double dearomative cycloaddition of arenes. Compared with the well‐known photodimerization of arenes under ultraviolet irradiation, the current reactions are carried out under mild conditions and feature wide substrate scope. A large array of structurally‐diverse polycyclic indoline derivatives is afforded in high yields (up to 98 %) with exclusive diastereoselectivity (>20:1 dr) via dearomative [4+2] or [2+2] pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Interestingly, inspired by the report of You group, [10f] a simple monitoring of the reaction by 1 H NMR showed that the dearomative cycloadditions of naphthalenes under visible‐light proceed in either [2+2] or [4+2] manifold (Figure 3). Another compound 34 a is characterized as the dearomative [2+2] adduct, which was observed rapid accumulation in the early stage of the reaction but gradual disappearance as the reaction proceeded.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, inspired by the report of You group, [10f] a simple monitoring of the reaction by 1 H NMR showed that the dearomative cycloadditions of naphthalenes under visible‐light proceed in either [2+2] or [4+2] manifold (Figure 3). Another compound 34 a is characterized as the dearomative [2+2] adduct, which was observed rapid accumulation in the early stage of the reaction but gradual disappearance as the reaction proceeded.…”
Section: Resultsmentioning
confidence: 99%
“…41 Scheme 36 Visible-light-induced intramolecular double dearomative cycloaddition of arenes. 42 Scheme 37 Photoredox asymmetric nucleophilic dearomatisation of indoles with neutral radicals. 43 Scheme 38 Organophotocatalytic dearomatisation of indoles, pyrroles and benzo(thio)furans via a Giese-type transformation.…”
Section: Photoredox Initiated Dearomatisationmentioning
confidence: 99%
“…Additionally, in 2021, You reported an intramolecular double dearomative [4 + 2] cycloaddition of indoles bearing a pendant 1-naphthyl ring ( Scheme 36 ). 42 Furthermore, a dearomative [2 + 2] cycloaddition reaction was facilitated when tethered heterocycles were introduced ( e.g. 2/3-furyl, 2-benzofuryl and 3-indolyl).…”
Section: Photoredox Initiated Dearomatisationmentioning
confidence: 99%
“…In this field, intensively exploring the synthetic utilities of transient, energetic, and highly reactive diradical species generated via ππ* excited indole rings is of much academic significance [4] . Using (hetero)arenes as acceptor of diradical species to get a high‐energy, transient double dearomative diradical (DDDR) species via ipso ‐cyclization, deserves investigation but has been rarely reported [5] …”
Section: Introductionmentioning
confidence: 99%